A combination of alkaline pH-shifting/acidic pH and thermal treatments improves the solubility and emulsification properties of wheat glutenin. (1st November 2022) - Jiang, Haihua; Pan, Junhui; Hu, Xing; Zhu, Miao; Gong, Deming; Zhang, Guowen
Highlights: Glutenin was modified by heating combined with pH-shifting/acidic pH. Combined heating/pH-shifting/acidic pH of glutenin increases α-helix content. Combined treatments increase solubility and emulsifying properties of glutenin. Abstract: Glutenin has limited applicability in food industry due to poor water solubility and emulsifying properties. In this study, the physicochemical properties of glutenin were improved by combined treatments of alkaline pH-shifting or acidic pH with heating. The surface morphology, structure and physicochemical properties were measured during the modification process of glutenin. Results showed that the smaller square clusters and regular tubular fibrils were observed in modified glutenin and the α-helix proportion of the treated glutenin was finally increased to 59.90 ± 0.01%. Compared with untreated glutenin, the combined treatments of pH-shifting with heating as well as fibrillation process increased the solubility of glutenin by 21.3 and 3.5 times, respectively. Moreover, the treated glutenin showed excellent emulsifying stability (EAI: 50.84 ± 0.51 m 2 g −1 ) and thermal stability (peak temperature increased from 109.58 to 149.05 °C). This study provides an informative basis for improving the physicochemical and functional properties of glutenin.